2016
DOI: 10.7860/jcdr/2016/19760.8140
|View full text |Cite
|
Sign up to set email alerts
|

Identification of HIV Mutation as Diagnostic Biomarker through Next Generation Sequencing

Abstract: The common mutations identified in this study were not previously reported, therefore suggesting the potential for them to be used for identification of viral infection, disease transmission and drug resistance. This was especially the case for, missense mutation S37N which could cause an amino acid change in viral proteases thus reducing the binding affinity of some protease inhibitors. Thus, the unique common mutations identified in this study could be used as diagnostic biomarkers to indicate the origin of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Five of those PR1 mutations (Q7K, L33I, L63I, C67A, and C95A) correspond to experimental mutations introduced to minimize autoproteolysis and to prevent cysteine-thiol oxidation of PR1 (Rosé, Salto, & Craikl, 1993). The three remaining PR1 mutations (K14R, S37N, and R41K) correspond to natural polymorphism mutations that were observed in HIV-1 strains isolated from treatmentnaïve and PI-experienced patients (Shaw et al, 2016;Descamps et al, 2009;Azam, Malik, A c c e p t e d M a n u s c r i p t the PR2 sequence set. This position has been reported as polymorphic with the mutation K57R (Damond et al, 2005).…”
Section: -Results and Discussionmentioning
confidence: 94%
“…Five of those PR1 mutations (Q7K, L33I, L63I, C67A, and C95A) correspond to experimental mutations introduced to minimize autoproteolysis and to prevent cysteine-thiol oxidation of PR1 (Rosé, Salto, & Craikl, 1993). The three remaining PR1 mutations (K14R, S37N, and R41K) correspond to natural polymorphism mutations that were observed in HIV-1 strains isolated from treatmentnaïve and PI-experienced patients (Shaw et al, 2016;Descamps et al, 2009;Azam, Malik, A c c e p t e d M a n u s c r i p t the PR2 sequence set. This position has been reported as polymorphic with the mutation K57R (Damond et al, 2005).…”
Section: -Results and Discussionmentioning
confidence: 94%
“…For instance, it was recently shown that NGS provides more precise HIV diagnosis with a better discrimination between different genotypes (Shaw et al . 2016 ). Furthermore, it can provide very high sensitivity for the diagnostics of rare pathogens, as shown with the identification of Leptospira as the causative agent of encephalitis after the failure of 38 different diagnostic tests (Wilson et al .…”
Section: Trends In Ngsmentioning
confidence: 99%
“…The common mutations identified at virus are located on the pol gene that codes for reverse transcriptase subunits [22]. Unlike other silent mutations, the missense mutation has more implications.…”
Section: Identification Of the Novel Biomarkers Through Ngsmentioning
confidence: 99%